PENGEMBANGAN MEDIA PENCATATAN TRANSAKSI KEUANGAN UNTUK PEMBUATAN LAPORAN LABA RUGI PADA USAHA KECIL - Ayu Astutik; Budi Mulyati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
This study aimed to (1) develop a record media for financial transactions for small businesses. (2) knowing the assessment from material experts, design experts and business practitioner experts on the financial recording media of the income statement in small businesses, (3) knowing the assessment from the grocery store owner on the financial recording media of the income statement. The method used in research was R&D. The research stage used was development research developed by Sugiyono with specifically modification stages, i.e. potential and problems, data collection, product design, design validation, design revision and product trial. This research was conducted at a small grocery store in Ranjeng Village, Ciruas District. The research result: The assesment from material expert showed the number of 3.37 (very good), the research results from the design expert showed the number of 4, (very good), and from the business practitioner showed number of 4 (excellent). The assessment response from small shop business owners showed an assessment that was in the range of 3.07 (good)-4 (very good). So it can be said that in general, the media developed was already good.